PEMAKNAAN TERHADAP FASHION STYLE REMAJA DI BANDUNG - Baruna Tyaswara; Reza Rizkina Taufik; Mahardiansyah Suhadi; Ratna Danyati (Universitas Bina Sarana Informatika, 2017)
Fashion in Indonesia has grown rapidly, such as technological developments that are increasingly growing days. Fashion is growing especially in the city of Bandung the more outlets, and clothing that was built in the city of Bandung. Teen styles can also reflect the attitude and behavior of the teenager. Fashion style among teenagers has become a culturally adaptation of western culture and not a bit of Bandung teenagers who love fashion style of western countries. The purpose of this study to know the meaning of the development of fashion and the meaning of how to fashion by teenagers in Bandung. The main informant in this research is adolescent in Bandung city. This study uses qualitative approach with study of phenomenology. The technique of data collection uses interview, observation and documentation. The finding result shows that The development of fashion with its existence in the present especially among teenagers in the city of Bandung which has a fashion trend can be regarded as a fashion barometer in major cities in Indonesia. Fashion is also an expression of self that allows everyone to try various roles in life. Keywords: fashion, social status, youth